The origins of yoga and tantra Indic religions to the thirteenth century - Samuel, Geoffrey (Cambridge University Press, 2008)
Yoga, tantra and other forms of Asian meditation are practised in modernized forms throughout the world today, but most introductions to Hinduism or Buddhism tell only part of the story of how they developed. This book is an interpretation of the history of Indic religions up to around 1200 CE, with particular focus on the development of yogic and tantric traditions. It assesses how much we really know about this period, and asks what sense we can make of the evolution of yogic and tantric practices, which were to become such central and important features of the Indic religious scene. Its originality lies in seeking to understand these traditions in terms of the total social and religious context of South Asian society during this period, including the religious practices of the general population with their close engagement with family, gender, economic life and other pragmatic concerns
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte Anfänge-1200; Geschichte; Yoga / History; Tantrism / History; Yoga; Tantrismus; Indien; India / Religion